Bixaceae of the Paraná State, Brazil - Antar, Guilherme Medeiros (2020)
This study provides a floristic survey of the Bixaceae from Paraná State. The family is represented in the area by two species: Cochlospermum regium (Mart. ex Schrank) Pilg., native from the remnants of the Cerrado biome, and Bixa orellana L., which has an uncertain origin but occurs sub-spontaneously in Paraná State. Descriptions, an identification key, photographs, and comments on the taxonomy of these species are provided.